2005
DOI: 10.1186/1742-2094-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Twitcher mouse (twi/twi) is an authentic murine model of Krabbe's disease. Accumulation of psychosine, resulting in apoptosis of oligodendrocytes and subsequent demyelination, is a cardinal event to the pathogenesis of this disease. Moreover, recruitment of inflammatory cells plays a significant role in the pathological process in the twi/twi central and peripheral nervous systems. In this study, we investigated the 1) the relationship between tumor necrosis factor-α (TNFα), pro-inflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Indeed, in our study, removal of the upregulated expressions of antigen presentation-related molecules such as CD11c (dendritic cell marker), MHC II, and CD80 and CD86 (costimulatory molecules for antigen presentation) was associated with the worsened pathology in twi+op mice, suggesting that the antigen presentation event is not a major contributing factor in the demyelinating pathology of GLD. Treatment of twi mice with ibudilast, a phosphodiesterase inhibitor which has been proven to suppress glial cell activation decreased the number of apoptotic OL and reduced demyelination (Kagitani-Shimono et al, 2005). Mohri et al (Mohri et al, 2006) have demonstrated reduced demyelination and some improved clinical signs in twi mice by blocking the pathway between an inflammatory mediator, prostaglandin D2 produced by microglia, and its receptors on astrocytes using gene targeting and pharmacological approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in our study, removal of the upregulated expressions of antigen presentation-related molecules such as CD11c (dendritic cell marker), MHC II, and CD80 and CD86 (costimulatory molecules for antigen presentation) was associated with the worsened pathology in twi+op mice, suggesting that the antigen presentation event is not a major contributing factor in the demyelinating pathology of GLD. Treatment of twi mice with ibudilast, a phosphodiesterase inhibitor which has been proven to suppress glial cell activation decreased the number of apoptotic OL and reduced demyelination (Kagitani-Shimono et al, 2005). Mohri et al (Mohri et al, 2006) have demonstrated reduced demyelination and some improved clinical signs in twi mice by blocking the pathway between an inflammatory mediator, prostaglandin D2 produced by microglia, and its receptors on astrocytes using gene targeting and pharmacological approaches.…”
Section: Discussionmentioning
confidence: 99%
“…or saline and killed 2 weeks later. The doses of doxorubicin and ibudilast were determined with reference to previous studies (Kagitani-Shimono et al, 2005;Poland, Hahn, Knapp, Beardsley, & Bowers, 2016;Shimauchi et al, 2017). Mice were killed by cervical dislocation, and tissues were removed and processed for histological examination or frozen for further analysis.…”
Section: Animal Modelmentioning
confidence: 99%
“…Recent studies have demonstrated that enzyme replacement therapy (ERT) [26, 27], substrate reduction therapy (SRT) [28], vector therapy [2931], and anti-inflammatory agents [32] improve the twitcher mouse pathology and modestly prolong lifespan. However, these therapeutic approaches are only partially successful even when combined with BMT [22, 29].…”
Section: Introductionmentioning
confidence: 99%